Relação entre teologia, filosofia natural e nova ciência em Giovanni Battista Riccioli (1598-1671) - Pinheiro, Maciel (2022)
This essay tries to analyse the way in which the jesuit priest Giovanni Battista Riccioli (1598-1671) and his ideas were evaluated by traditional and modern Historiographies, from seventeenth to tweentieth century, in secular and ecclesiastic ambiances in Italy, having in mind the possibiliy of historical forgetfulness of the contribution this jesuit offered to modern science in his century. For this, the use of Contextual, Historiographic and Epistemologic approaches seecked to understand more deeply the man Riccioly, his ideas in the debates of his time, from his Cosmology, Jesuit Mystic, Education according to the contemporary Ratio Studiorum and Position in Jesuit Order. In fact, he established an interchange of speech among Theologians, Philosophers and Mathematicians, relating Scholastic Theology, Natural Philosophy and New Science, elaborating an solid scientific knowledge which didn’t contradict the Holy Scriptures